Transfusion Approaches and Mortality in Trauma Patients: A Narrative Review - Fries, Dietmar; Innerhofer, Petra; Spahn, Donat R. (Seminars in Thrombosis and Hemostasis, 2017)
Trauma is one of the leading causes of mortality in the world, accounting for millions of deaths per year. One of the most frequent causes of death in trauma patients is hemorrhage. The presence of a coagulopathy in trauma patients more than doubles the expected mortality. Coagulation management is a key aspect of care for bleeding trauma patients and has been investigated in many studies. However, it is unclear whether a particular approach to coagulation management is associated with a reduction in mortality. Treatment may be guided (e.g., viscoelastic test-guided administration of coagulation factor concentrates) or nonguided (e.g., treatment with a fixed ratio of plasma:red blood cells). This review aimed to assess the published literature regarding coagulation management technique and mortality rate. From the 41 articles obtained in the literature search, there appeared to be a trend toward lower mortality in studies utilizing a guided approach, despite a higher injury severity score in these patients. There were many methodological variations across studies including coagulation management approaches, inclusion criteria, time and type of measurements, use of early fast coagulation monitoring and damage control surgery principles, additional products to those under study, and potential regional differences. It is essential that controlled trials are performed to ascertain optimal transfusion approaches in trauma patients.
Keywords: trauma; coagulation; hemostasis; mortality; transfusion